English as a plural language: The significance of Yamuna Kachru. Issue 1 (March 2015) - SRIDHAR, S. N; SRIDHAR, KAMAL K.; SMITH, LARRY E.; SRIDHAR, S.N.
ABSTRACT In a distinguished career spanning five decades Professor Yamuna Kachru enriched several areas of linguistics and applied language studies. This initial appreciation attempts to show how her family background, education, and experience on three continents shaped her interests and perspectives. The evolution of her research is structured as a series of concentric circles, each informed by the previous ones. The inner circle is her monumental work on Hindi grammar and sociolinguistics. The second circle concerns contrastive analysis, second language acquisition and teaching, and multilingualism. The third circle involves pragmatics, discourse structure, and world Englishes. The salient features of her scholarship are outlined, along with her vital role in bringing about world‐wide recognition of the new paradigm of world Englishes through original research, teaching, and building the academic infrastructure for the field through texts, reference works, the journal World Englishes, and the professional society IAWE.